Vanadate prevents glucocorticoid-induced apoptosis of osteoblasts in vitro and osteocytes in vivo. - Conradie, M; De Wet, H; Kotze, D; Burrin, J; Hough, F; Hulley, P (2007)
Skeletal mass is maintained by a balance between formation and resorption, cell proliferation and apoptosis. In vitro, glucocorticoids (GCs) decrease extracellular signal-regulated kinases (ERK) activation by mitogens, thus inhibiting osteoblast proliferation. Both ERK activity and proliferation are restored by co-treatment with the protein tyrosine phosphatase inhibitor, vanadate. Since ERK signalling may also be anti-apoptotic, we explored the effects of vanadate on GC-induced apoptosis in vitro and in vivo. Apoptosis in MBA-15.4 pre-osteoblasts increased from 6 h and remained up to eightfold higher through 6 days of 10(- 6) M dexamethasone (Dex) treatment. Co-incubation with 10(- 7) M vanadate markedly reduced apoptosis at all time points. Vanadate also prevented GC-induced poly-ADP-ribose polymerase cleavage. We assessed the transcriptional profiles of seven anti-apoptotic proteins (Bcl-2, Bcl-X(L), inhibitors of apoptosis protein-1 (IAP-1), IAP-2, X-linked IAP (XIAP), Fas-associated death-domain-like IL-1beta-converting enzyme-inhibitory protein (FLIP(Long)) and FLIP(Short)) in osteoblasts subjected to various stimuli using real-time quantitative PCR. Although these anti-apoptotic genes responded to different mitogenic conditions, Dex failed to repress their expression, and in fact significantly up-regulated Bcl-X(L), IAP-2 and XIAP. Dex may therefore induce apoptosis by up-regulating pro-apoptotic gene expression. We have previously demonstrated that rats treated with GC develop low formation osteoporosis (bone histomorphometry and DEXA) and skeletal fragility (breaking strength) that were largely prevented by co-treatment with vanadate. We report here that vertebrae from rats treated with 3.5 mg/kg per day methylprednisolone for 9 weeks showed increased incidence of terminal deoxynucleotidyl transferase-mediated biotin-dUTP nick end-labelling-positive apoptotic osteocytes, which was reduced by vanadate co-treatment. We conclude that vanadate prevents GC-induced apoptosis of pre-osteoblasts in vitro and osteocytes in vivo, and this may contribute to its bone-sparing effects in vivo.